External Validity and the New Inductivism in Experimental Economics - Gadenne, Volker; Justus Liebig University Giessen (My University, 2013)
The idea of external validity, which is well-known in the social sciences, has recently also been emphasized in experimental economics. It has been argued that external validity is an important criterion in experimental research, which has been neglected by philosophy of science. In connection with this criterion, a methodology has been advanced in which inductive generalization and analogical inference play a central role. The hypotheticodeductive methodology is said to be untenable, or at least insufficient. In this paper, hypothetico-deductivism is defended. The idea of external validity, and the new plea for inductivism, is critically discussed. It is pointed out that the fundamental problems of inductivism are still unsolved. The criterion of external validity is superfluous and misleading. And the problems in experimental research associated with external validity can well be solved on the basis of deductivism.
Keywords: ddc:100; ddc:330